A Male Neonate with Congenital Adrenal Hyperplasia: A Case Report - Parvin, Ruma; Ghosh, Nobo Krishna; Mahbuba, Sharmin; Chudhury, Farhana Jaya; Ferdoucy, Sultana Amena (Dhaka Shishu (Children) Hospital Journal, 2021)
Abstract not available DS (Child) H J 2020; 36(1) : 75-77